Geoheritage and geoconservation: the challenges - Brilha, J. B. (2018)
An updated and broad perspective of geoheritage, its values and threats, and examples of how it can be protected and managed is presented in the previous chapters by many experts from all conti- nents. Based on the present situation of geoheritage and geoconservation at the international, national and local levels, this last chapter proposes possible guidelines for future work and develop- ment of these topics. It is a personal perspective of the authors about the main challenges that should be addressed by international agencies and the scientific community, national administra- tions and local actors, aiming to strengthen the role of geoheritage and geoconservation in our societies.